2015
DOI: 10.1120/jacmp.v16i6.5530
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Knife radiosurgery with CT image‐based dose calculation

Abstract: The Leksell GammaPlan software version 10 introduces a CT image‐based segmentation tool for automatic skull definition and a convolution dose calculation algorithm for tissue inhomogeneity correction. The purpose of this work was to evaluate the impact of these new approaches on routine clinical Gamma Knife treatment planning. Sixty‐five patients who underwent CT image‐guided Gamma Knife radiosurgeries at the University of Pittsburgh Medical Center in recent years were retrospectively investigated. The diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…These were compared with the dose distributions obtained by setting all structures to the physical constants for water (MC-water), which are similar to the assumptions used by the TMR 10-based treatment algorithm in LGP. 55 The dose distributions MC-Onyx and MC-water were compared via a variety of dose metrics, including minimum/mean/maximum dose to the nidus, prescription isodose volume, selectivity index (TV PIV /PIV), coverage index (TV PIV /TV), and gradient index (PIV half /PIV), where PIV is the prescription isodose volume, TV PIV is the volume of nidus covered by the prescription isodose volume, and PIV half is the volume of the isodose surface that is onehalf of the prescription isodose. 31,32 All dose metrics were calculated in terms of percentage isodoses (i.e., percentage of maximum dose).…”
Section: Monte Carlo Analysismentioning
confidence: 99%
“…These were compared with the dose distributions obtained by setting all structures to the physical constants for water (MC-water), which are similar to the assumptions used by the TMR 10-based treatment algorithm in LGP. 55 The dose distributions MC-Onyx and MC-water were compared via a variety of dose metrics, including minimum/mean/maximum dose to the nidus, prescription isodose volume, selectivity index (TV PIV /PIV), coverage index (TV PIV /TV), and gradient index (PIV half /PIV), where PIV is the prescription isodose volume, TV PIV is the volume of nidus covered by the prescription isodose volume, and PIV half is the volume of the isodose surface that is onehalf of the prescription isodose. 31,32 All dose metrics were calculated in terms of percentage isodoses (i.e., percentage of maximum dose).…”
Section: Monte Carlo Analysismentioning
confidence: 99%
“…The difference between the two techniques will be larger in cases where the scalp is thick and non-existent in, e.g., an elderly patient with thinned scalp particularly if they are bald. Former studies using LGK Perfexion™ and 4C™ devices, such as Xu et al study, reported the same range of discrepancy (2.5%) between the two skull contour definition techniques [14], as did the team of Kobayashi et al (2%) [6]. Rojas-Villabona et al also reported an increase of BOT of 1.45% with head contours derived from the CT scan [8].…”
Section: Beam-on Time Increasementioning
confidence: 72%
“…These algorithms have been compared in previous studies. [4][5][6][7][8] It was found that the convolution algorithm provided greater accuracy to films within a RANDO phantom to dose distributions than that with TMR10. 4 This conclusion was supported by Nakazawa et al, 5 who advocated the use of convolution algorithm to reduce dosimetric uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…7 Treatment times were studied in one paper revealing an 8•4% larger average treatment times for identical prescriptions and shot arrangements when the convolution dose calculation was used compared to the TMR10 algorithm. 8 When implementing new dose calculation algorithms, special considerations must be given to the dose prescription. The traditional doses prescribed by radiation oncologists have been based on protocols using dose calculations where the entire scalp is treated as water.…”
Section: Introductionmentioning
confidence: 99%